Echocardiographic index E/e’ in association with cerebral white matter hyperintensity progression - Lee, Woo-Jin (PLoS One, 2020)
Cerebral white-matter hyperintensities (WMHs) on MRI is associated with reduced compliance of the cerebral arterioles. We hypothesized that an echocardiography index for left ventricular (LV) diastolic function, E/e’, might reflect the cerebral arteriolar compliance and evaluated the association between E/e’ and long-term progression rate of the cerebral WMH volume. This retrospective study included individuals who were ≥ 50 years of age, with a preserved LV ejection fraction (≥ 50%) and neurological function status (modified Rankin scale score ≤1), and underwent initial and follow-up MRI evaluations within intervals of 34–45 months. Baseline clinical, laboratory, and echocardiography markers such as ejection fraction, LV mass index, and E/e' were obtained. WMH volume progression rate between the baseline and follow-up MRIs was designated as the outcome factor. 392 individuals (57.1% men; mean age: 66.7±8.4 years) were followed-up for 38.2±3.4 months. The mean WMH volume progression rate was 1.35±2.65 mL/year. The log-transformed value of WMH volume progression rate was linearly associated with the log-transformed E/e’ (B coefficient = 0.365; 95% confidence interval [CI] 0.180−0.551; P = 0.001), along with the log-transformed values of baseline WMH volume (B = 0.142; 95% CI 0.106−0.179; P<0.001) and glomerular filtration rate (B = -0.182; 95% CI -0.321−0.044; P = 0.010). Additionally, a subgroup with an E/e’ ≥15 exhibited a significantly higher WMH progression rate compared to the subgroups with lower E/e’ values (P<0.001), especially in the lower quartiles (quartiles 1 and 2) of the baseline WMH volume. We concluded that echocardiographic marker E/e’ is associated with the long-term progression rate of cerebral WMHs in population with preserved LV systolic function.